Impaired Left and Right Ventricular Systolic and Diastolic Function in Response to Exercise in Patients with Diastolic Dysfunction. Issue 8 (31st May 2016) - Narayanan, Meena; Bamba, Alyssa; Liu, Shuang; Naqvi, Tasneem Z.
Abstract : Background: Diastolic dysfunction (DD) is associated with exercise intolerance. To evaluate mechanisms of exercise intolerance in patients with DD, we performed bicycle stress echocardiography. Method and Results: Doppler measurements were performed at baseline, during exercise and recovery in 26 patients (58 ± 11 years) with DD and normal left ventricular ejection fraction and 6 normal controls (53 ± 5 years). Compared to controls, patients achieved similar target heart rates but lower METs (5.5 ± 2 vs. 9.8 ± 3, P < 0.01) and a higher peak pulmonary artery pressure (PAP) at peak exercise (50 ± 13 vs. 32 ± 7 mmHg, P < 0.01) despite similar PAP at rest and similar mean blood pressure at peak exercise (110.4 ± 18.0 vs. 106.9 ± 11.4 mmHg, P = NS). In patients versus controls, mitral E/E' was similar at baseline (10 ± 3 vs. 8 ± 1.3, P = NS) but higher at recovery (11 ± 2 vs. 7 ± 2, P < 0.05), % mitral filling time was shorter at baseline, onset, and peak exercise, whereas % LV and RV ejection time was similar to controls throughout exercise. Compared to controls, lateral mitral annular S' (11.8 ± 2.5 cm/sec vs. 14.9 ± 1.9 cm/sec, P < 0.02) and tricuspid annular S' (14.8 ± 4.1 cm/sec vs. 19.4 ± 4.0 cm/sec, P < 0.05) were lower at peak exercise in patients. Conclusion: Diastolic filling time is reduced at rest and stress while LV ejection time increases normally during exercise in DD. There is a reduced systolic reserve in LV and RV during exercise in DD. These mechanisms contribute to exercise intolerance and elevation of left atrial and PAP in patients with DD.